Rats Prone to Obesity Under a High-Carbohydrate Diet have Increased Post-Meal CCK mRNA Expression and Characteristics of Rats Fed a High-Glycemic Index Diet - Chaumontet, Catherine; Azzout-Marniche, Dalila; Blais, Anne; Chalvon-Dermersay, Tristan; Nadkarni, Nachiket A.; Piedcoq, Julien; Fromentin, Gilles; Tomé, Daniel; Even, Patrick C. (Frontiers in Nutrition, 2015)
We previously reported that rats prone to obesity exhibit an exaggerated increase in glucose oxidation and an exaggerated decline in lipid oxidation under a low-fat high-carbohydrate (LF/HC) diet. The aim of the present study was to investigate the mechanisms involved in these metabolic dysregulations. After a one week adaptation to laboratory conditions, 48 male Wistar rats were fed a LF/HC diet for 3 weeks. During weeks 2 and 3, glucose tolerance tests (GTT), insulin tolerance tests (ITT) and meal tolerance tests (MTT) were performed to evaluate blood glucose, plasma and insulin. Glucose and lipid oxidation were also assayed during the GTT. At the end of the study, body composition was measured in all the rats, and they were classified as carbohydrate resistant (CR) or carbohydrate sensitive (CS) according to their adiposity. Before sacrifice, 24 of the 48 rats received a calibrated LF/HC meal. Liver, muscle and intestine tissue samples were taken to measure mRNA expression of key genes involved in glucose, lipid and protein metabolism. ITT, GTT and MTT showed that CS rats were neither insulin resistant nor glucose intolerant, but mRNA expression of CCK in the duodenum was higher and that of CPT1, PPARα and PGC1α in liver were lower than in CR rats. From these results, we make the hypothesis that in CS rats, CCK increased pancreatic secretion which may favor a quicker absorption of carbohydrates and consequently induces an enhanced inhibition of lipid oxidation in the liver leading to a progressive accumulation of fat preferentially in visceral deposits. Such a mechanism may explain why CS rats share many characteristics observed in rats fed a high glycemic index diet.